Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

This question recently came up in a competitive exam and I have been struggling to find out the easiest way to solve it.

Given that $x = 2+3\sqrt{3}$, what is the value of $x^4 + 1/x^4$.

Could someone provide me with an approach other than the direct approach of multiplying $x$ to itself $4$ times and adding it to its reciprocal.

Thanks in advance!

share|cite|improve this question

Hint: $\big(x+1/x\big)^2=x^2+1/x^2+2$ so $$x^2+1/x^2=(x+1/x)^2-2$$ but $$(x^2+1/x^2)^2=(x^4+1/x^4)-2$$ I think you can do the rest.

share|cite|improve this answer
One can both exploit the innate symmetry and preserve some of the innate structure to get a more concise result - see my answer. – Bill Dubuque Oct 13 '12 at 15:59
Helpful hint! +1 $\ddot\smile$ – amWhy Feb 28 '13 at 14:37

Hint $\ $ Compute $\rm\: x^4 = (x^2)^2\! = \color{#C00}a+\color{#0A0}b\sqrt{d}\ $ so $\rm\:\bar x^4 = a-b\sqrt{d}.\ $ Let $\rm\,n = x\bar x.\:$ Therefore

$$\rm x^4 + \frac{1}{x^4}\, =\, x^4 + \frac{\bar x^4}{(x\bar x)^4}\, =\, x^4 + \frac{\bar x^4}{n^4 }\, =\, (\color{#C00}a(n^4\!+1) +\, \color{#0A0}b(n^4\!-1)\sqrt{d})/n^4$$

Here $\rm\: x^4 = (x^2)^2\! = (31+12\sqrt{3})^2\! = 1393+744\sqrt{3}\ $ so $\rm\:\color{#C00}a=1393,\ \color{#0A0}b = 744,\: $ and $\rm\,n = x\bar x = -23.$

Remark $\ $ As I mentioned in the closely related question, one can also employ (Newton) identities for symmetric functions (see also Babak's answer). However, in this example, that method, done rotely, will require doing more (large) integer arithmetic, and it will result in a less concise answer, since it does not preserve the $\rm\:n^4\!\pm 1\:$ structure in the result.

share|cite|improve this answer

You the thing you need to calculate is $x^4$.

You start by isolating the square root $x = 2+3\sqrt{3} \Leftrightarrow x - 2 = 3\sqrt{3}$

Then you square both sides $(x - 2)^2 = (3\sqrt{3})^2 \Leftrightarrow x^2 - 4x + 4 = 27 \Leftrightarrow x^2 - 4x -23 = 0$

Let $P$ be $X^4$

Let $D$ be $X^2 - 4X - 23$

Now, you compute $R$, the remainder of the euclidean division of $P$ by $D$. I get $R = 248X+897$

If you name $Q$ the quotient, you have $P = D\times Q + R$. You don't need it but I get $X^2+4X+39$

But for your given $x$, $D$ evaluates to $0$ so $P$ evaluates to the same value as $R$. $( X^2+4X+39 ) \times (X^2 - 4X - 23)+ (248X+897) = X^4$

So $X^4 = 1393+744 \sqrt 3$

Then $X^4 + \frac{1}{X^4} = \frac{(X^4)^2+1}{X^4}$ and you finally get $\frac{2 \times (1800529+1036392 \sqrt 3))}{(1393+744\sqrt3)}$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.